Transition Metal (II) Coordination Chemistry Ligated by a New Coplanar Tridentate Ligand, 2,6-Bis(5-isopropyl-1H-pyrazol-3-yl)pyridine - Kiyoshi Fujisawa; Yurika Minakawa; David James Young (Inorganics)
Transition metal (II) complexes stabilized by 2,6-di(pyrazol-3-yl)pyridine as a novel coplanar tridentate nitrogen-donor ligand have been reported for their unusual structures and photoluminescent properties. In this work, the ligand 2,6-bis(5-isopropyl-1H-pyrazole-3-yl)pyridine (denoted as L) and its transition metal (II) halogenido complexes viz [ZnCl2(L)] (1), [ZnBr2(L)] (2), [CuCl2(L)] (3), and [CuCl(L)(thf)](PF6) (4) were synthesized and characterized by single crystal X-ray crystal analysis. Its structures contained N–H groups in its pyrazole rings and hydrogen bonds between these N–H donors and the coordinated halogenide ions and lattice solvent molecules. Tautomers between 3-pyridyl and 5-pyridyl substitutes were also observed. In L, the N–H group at the pyrazole nitrogen was located adjacent to the pyridine ring to form hydrogen bonds with adjacent pyrazoles. However, on complexation, the H atoms at the pyrazole nitrogens are shifted remotely to the pyridine. The zinc (II) complexes [ZnCl2(L)] (1) and [ZnBr2(L)] (2) possessed distorted trigonal pyramidal structures in the solid state. By comparison, the copper (II) complexes [CuCl2(L)] (3) and [CuCl(L)(thf)](PF6) (4) adopted square pyramidal geometry with a Jahn–Teller distortion resulting from their d9 electron configurations.